Education Technology for Effective Teachers - Evans, David K. (World Bank, Washington, DC, 2021)
Education systems around the world are investing in technology to help teachers be more effective. In some cases, the results are exciting. In others, the impact of technology falls short of expectations or remains unevaluated. The closing of schools worldwide due to the COVID-19 pandemic has highlighted the importance of understanding how to leverage technology well. This note lays out four principles for investing in technology for effective teachers and six aspects of teaching where technology can boost teacher performance, together with examples of tested, promising, and cautionary experiences with teacher technologies.